Peranan dan Tanggungjawab Ibu Bapa dalam Pengasuhan Anak dan Remaja - Habibie Ibrahim; Mazni Mustapha; Joki Perdani Sawai; Nurul Hudani Md Nawi; Puteri Hayati Megat Ahmad (Asian Social Work Journal, 2018)
This conceptual paper emphasizes roles and responsibilities of parents towards children particularly teenagers. Currently, Malaysia shows an increasing of teenagers’ involvement in social problems. The increasing of social problem is believed due to lack of roles and responsibilities played by parents especially for dual-career families. Besides that other problem contributed to the increasing of social problems was less communication between parents and children. Therefore, this paper also emphasizes the role of communication in effort to build a good and harmoniousrelationship between parents and teenagers and outlines the roles and responsibilities of parents towards children and families.